Fuentes de sobre-costos y distorsiones en las empresas eléctricas públicas en México - Eduardo Martínez Chombo (Banco de México, 2009)
– This paper describes and tries to quantify the effects of some factors that have affected costs of state owned electric utilities in Mexico (energy losses, fuel and labor). It is noted that the impact of the increases in fuel prices on the electric utilities' total cost in the last years has been important. However, the over-cost associated to energy losses and labor is also significant and comparable to the impact of the increase in fuel prices. The structure of cross subsidies in the industry is also described, pointing out that it is complex and makes the performance evaluation of the state owned electric utilities difficult.
Keywords: H54; Q48; 330; electricity sector; state-owned utility; energy losses; CFE; LyFC; Elektrizitätswirtschaft; Öffentliches Unternehmen; Produktionskosten; Mexiko